2014
DOI: 10.1519/jsc.0000000000000547
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Strength Characteristics to Change of Direction and Agility Performance in Female Basketball Athletes

Abstract: Research has often examined the relationship between 1 or 2 measures of strength and change of direction (COD) ability reporting inconsistent relationships to performance. These inconsistencies may be the result of the strength assessment used and the assumption that 1 measure of strength can represent all "types" of strength required during a COD task. Therefore the purpose of this study was to determine the relationship between several lower-body strength and power measures, COD, and agility performance. Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
335
7
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(377 citation statements)
references
References 23 publications
23
335
7
12
Order By: Relevance
“…38 These findings are consistent with Hori et al 16 who found significant negative correlations between 1RM front squat and modified 505 performance. In addition, our findings are consistent with the work of Spiteri et al 15 , in that IPF during the IMTP showed significant relationships to COD performance. Sprinting and COD requires acceleration of body mass, and is highly dependent upon absolute strength levels, with research showing transfer effects from long-term periodized strength training to positively improve COD performance.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…38 These findings are consistent with Hori et al 16 who found significant negative correlations between 1RM front squat and modified 505 performance. In addition, our findings are consistent with the work of Spiteri et al 15 , in that IPF during the IMTP showed significant relationships to COD performance. Sprinting and COD requires acceleration of body mass, and is highly dependent upon absolute strength levels, with research showing transfer effects from long-term periodized strength training to positively improve COD performance.…”
Section: Discussionsupporting
confidence: 93%
“…Tillin et al 14 found normalized PF at 100 ms during an isometric back squat to correlate to 5-and 20-m sprint performance in rugby players. In addition, Spiteri et al 15 found a significant correlation (r = 0.79) between IPF during the IMTP and 505 COD performance in female basketball athletes.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Also, no technique or strength measures were assessed within the current study, however previous research in female basketball athletes show faster athletes apply increased braking forces and shorter ground contact times during 505 performances. [36][37][38] Additionally, the same authors found faster athletes to observe greater eccentric and isometric strength values as compared to slower athletes. Therefore, differences in 505 performances between age categories may be attributed to superior movement mechanics and strength capacity.…”
Section: Discussionmentioning
confidence: 86%
“…To enable objective performance criteria for use in athlete-practitioner decision making during the rehabilitation process [14] appropriate agility tests are required. A major hurdle to overcome in implementing agility performance tests with athletes or applying during injury rehabilitation is the need for force plates [16], timing gates [17] and expensive camera systems [6,17]. The aims of this study were to assess the reliability and practicality of implementing a field based agility test encompassing perceptual-agility action performance.…”
Section: Introductionmentioning
confidence: 99%